2017
DOI: 10.1590/1806-9282.63.08.717
|View full text |Cite
|
Sign up to set email alerts
|

Is a safety guidewire needed for retrograde ureteroscopy?

Abstract: Introduction:It is generally advised to have a safety guidewire (SGW) present during ureteroscopy (URS) to manage possible complications. However, it increases the strenght needed to insert and retract the endoscope during the procedure, and, currently, there is a lack of solid data supporting the need for SGW in all procedures. We reviewed the literature about SGW utilization during URS. Method: A review of the literature was conducted through April 2017 using PubMed, Ovid, and The Cochrane Library databases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Currently, there is a lack of solid data supporting the need for safety guidewire insertion in all procedures. 4 A randomized controlled trial suggests that safety guidewire substantially increased the resistance against moving a semi-rigid ureteroscope up and down the ureter. The safety guidewire may thus be an obstacle to the ureteroscopic procedure and may even increase the risk of harming the ureter in some patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is a lack of solid data supporting the need for safety guidewire insertion in all procedures. 4 A randomized controlled trial suggests that safety guidewire substantially increased the resistance against moving a semi-rigid ureteroscope up and down the ureter. The safety guidewire may thus be an obstacle to the ureteroscopic procedure and may even increase the risk of harming the ureter in some patients.…”
Section: Introductionmentioning
confidence: 99%
“…Expected complicated surgery such as impacted stones or anatomical abnormalities, narrow ureteral caliber, ectopic kidney, severe ureteral edema, lack of optimal visibility 4…”
Section: Introductionmentioning
confidence: 99%
“…This meta-analysis recommended further comparative studies on stone clearance rate in patients with distal ureteric stones, undergoing URS with and without SGW. 7,8 As no local studies were found in the literature. So, this study was aimed to compare the stone clearance rate in patients with distal ureteric stones undergoing URS with and without SGW.…”
Section: Introductionmentioning
confidence: 99%